Category of Modality in Belles-lettres and Journalistic Styles - Panasenko, Nataliya; Pravdová, Hana; Kryachkov, Dmitry (Journal of History Culture and Art Research, 2020)
The article presents the results of a comparative analysis of subjective modality in literary and media texts. Subjective modality is connected with the speaker's attitude to the statement. In the text, it is realized in the form of the so-called modal meanings. We compare the ways of expressing subjective modality in the texts belonging to different functional styles: belles-lettres (emotive prose, drama, poetry), newspaper, and publicistic. We have chosen examples from fiction as well as from media texts, because we suppose that the modal meanings they convey depend on lexical and grammatical means of expressing subjective modality in the text; if it is a recorded text than the major role belongs to intonation. If modal markers can be found in the whole text, one can speak of the so-called 'diffuse modality'. The results of our analysis show that it is possible to single out three types of modal meanings forming three groups: group A – speaker's attitude to the content of the speech, group B – speaker's attitude to the addressee; group C – the attitude of the speaker towards themselves. Modal markers are mainly concentrated in leading segments of the text. In most of the texts, these means of expressing text modality are connected with text genre, especially in media texts, which belong to rational and emotional journalism. In media texts, subjective modality is often displayed by various communicative manipulative strategies used to form the public opinion.